The effectiveness of neuromuscular electrical stimulation on pain, function, and quadriceps muscle strength in adults with patellofemoral pain: A systematic review and meta-analysis - Ahmed Ibrahim Abdelhamed; Hossam Mortada; Ahmed Hendawy; Amr Elfeky; Roshdy M. Kamel; Shorouk Elshennawy (BMC Musculoskeletal Disorders)
Abstract Background Patellofemoral pain (PFP) is a chronic musculoskeletal disorder, with Neuromuscular electrical stimulation (NMES) often used as a complementary treatment option, however no definitive evidence supports its benefits. This systematic review aimed to evaluate the efficacy of adding NMES to exercise programs for treating PFP. Methods PubMed, Cochrane CENTRAL, Web of Science, Scopus, PEDro, ClinicalTrails.gov and International Clinical Trials Registry Platform were searched up to July 2024 for randomized controlled trials (RCTs) investigating the effectiveness of NMES in people with PFP. Two researchers independently screened titles and abstracts; another pair filtered full-text articles. The studies had to report pain, functionality, and strength as outcome measures. The risk of bias was assessed using the revised Cochrane Collaboration tool (RoB 2.0). Meta-analysis was conducted using RevMan 5.4.1 software, and the quality of evidence was evaluated using the GRADE approach. Results Eleven RCTs, involving 571 participants, were included. Most of the studies were of high risk of bias. NMES combined with exercise was favored in the long course for improving function (SMD: 3.74, 95% CI 1.35, 5.81; P = 0.0004) and quadriceps muscle strength (SMD: 0.53, 95% CI 0.18, 0.89; P = 0.003) compared to exercise; however, it did not differ from exercise in relieving pain and improving EMG activity level, and participation. The GRADE certainty rating of the results was rated as very low mostly due to inconsistency and high risk of bias. Conclusion Very low certainty of evidence suggests that adding NMES to an exercise program may improve the knee joint function and quadriceps strength with treatment courses of six weeks or more in patients with PFP, but it is not superior to control for reliving pain and improving EMG activity, activity level, and participation. Larger, high-quality RCTs on the long-term are needed to reach an incisive conclusion. Registration: The protocol was registered at Open Science Framework Register under https://doi.org/10.17605/OSF.IO/Y2JUZ .